APPLICABILITY AND BENEFITS OF SOFTWARE AND SIMULATORS IN TEACHING LEARNING PROCESSES - Celestino, Marcelo Salvador [UNESP]; Pires Nogueira Valente, Vania Cristina [UNESP] (Univ Estadual Campinas, Fac Educacao, 2021)
The aim of this paper was to identify the applicability and benefits of softwares, simulation processes and simulators for the educational practice in different contexts. The text presented here integrated the theoretical foundation and made possible the master's dissertation entitled Applicability of simulation software for the teaching of Computed Tomography for technicians and technologists in Radiology. The consulted literature shows the applicability of the simulation and its aspects in different areas, such as management, industry, automotive, military, health, among others, with educational focus. The benefits described in the literature refer to the acquisition of skills, the development of skills, the exhaustive repetition of an activity without harm or risk to patients, the low cost, among others, through software and simulators, and emphasize its use as tools to support the teacher for teaching-learning.
Keywords: Education; Software; Simulation Techniques; Media Education; Technology